Disaster Risk Governance in Indonesia and Myanmar: The Practice of Co-Governance - Srikandini, Annisa Gita (2018)
This article discusses the discourse and practice of co-governance in disaster risk reduction (DRR). It is based on an extensive ethnographic study of DRR at global level and in two disaster-prone countries in Southeast Asia: Indonesia and Myanmar. These country cases were selected not only because of their similarly high vulnerability to disasters, but also because the overlaps and differences between them in disaster governance allowed for a comparative study of the impacts of co-governance in DRR. Indonesia is characterised by a longer history with democratic governance institutions and a largely national-led response to disasters; Myanmar has only started to develop DRR in the last 10 years, and its policies are still largely led by international actors. In both countries, disaster response has shifted from being top-down and state-centred to following a co-governance approach. This reflects a worldwide trend in DRR, the idea being that co-governance, where different state and non-state stakeholders are involved in governance networks, will lead to more inclusive and effective DRR. Our findings suggest that, in Myanmar and Indonesia, DRR has indeed become more inclusive. However, at the same time, we find that DRR in both countries has remained highly hierarchical and state-centred. Although the possible gains of encouraging future initiatives among different actors negotiating disaster response is under-explored, we find that, to date, the multiplication of actors involved in DRR, especially within the state, has led to an increasingly complex, competitive system that negatively affects the ability to conduct DRR.